RESPON PELANGGAN PADA SITUS TRIPADVISOR.COM SEBAGAI BENTUK CYBER PUBLIC RELATIONS THE PREMIERE HOTEL PEKANBARU - Afifah, Adilla; Yazid, Tantri Puspita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tripadvisor.com is a site that aims to facilitate the tourists to seek information about lodging such as hotels. By using this site everyone is free to provide feedback and reviews based on their experiences, both positive reviews and negative. Many reviews on this site will indirectly affect customers or prospective customers in selecting and deciding hotel. Reviews on these sites influence for customers and prospective customers in selecting place to stay, the PR The Premiere use the site as a form of Cyber PR in The Premiere Hotel Pekanbaru. The purpose of this study was to determine how the customer response to the tripadvisor.com site as a form of Cyber PR activity The Premiere Hotel Pekanbaru. This study uses descriptive qualitative research method. This study aim to describe and illustrate the object based on facts by using infroman as a data source. The Informant are 6 people consisting of one PR The Premiere Hotel and 5 customers who are selected based on purposive sampling. Data collection techniques are observation, interviews, and documentation. These results indicate that the customers response to the tripadvisor.com website is a form of stimulus provided by the customer to the hotel Premiere Pekanbaru written based on the experience perceived by the customer, which he poured into the tripadvisor.com site. This is done by the customer is motivated because of the desire of customers to share information with customers and prospective customers others. A good reciews will sure be a selling point for the hotel, but bad reviews would certainly make the hotel into an ugly image. Respond to customer reviews on tripadvisor.com site as a form of cyber PR can be said to be appropriate and effective, the PR can form the image the hotel who care and want to know to the customers. Furthermore, by responding to customer reviews on tripadvisor.com site can be seen and perceived by customers and prospective customers who ends will have an impact on the marketing activities of the hotel. Keywords: Customer Response, Cyber Public Relations, Tripadvisor.com